KELOMPOK USAHA LAS LISTRIK DENGAN TEKNIK DESAIN ORNAMEN TERALIS PAGAR BERBASIS KOMPUTER - Suryanto, Agus; Hudallah, Nur; Putri, Riana Defi Mahadji (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
In some districts in Semarang, there are many businessmen in the field of Electrical Welding (SMEs) and the like, although the number is quite large and spread but the potential is not yet developed optimally. From the observation in the field of potential small and medium scale home industry in the field of Electrical Welding in Semarang area has not been much touched by the advancement of design technology by utilizing IT (computer) and application software to enrich its ornament design. Based on the survey and direct interviews in several household industries in the field of electric welding spread in Semarang region, the problems faced can be grouped into three aspects, namely the human resources improvement facility that is the knowledge of technological improvement in the field of fence ornament design and trellis, , and management of production management in the field of Las liistrik where the three aspects are interrelated. This activity aims to answer the existing problems, namely training and tutorial techniques trellis ornament design and fence with computer technology and its application. Improving embroidery design facilities in the form of software applications ornaments trellis design and fence and software application tools. Output targets that can be generated from this activity are: 1) Holding training and tutorial about design technique of electric weld ornament with computer technology, 2)Produce various design patterns of trellis ornaments and computerized fencing, 3) Business model management model of electric weld field managed professionally capable of improving product quality and quantity, 4) Increasing synergy between universities and business community in Semarang, 5) Produce scientific articles in national journal in order to publish the results of the activity